Fundamental Factors Affecting Financial Performance of Cooperative - Sudarmi Sudarmi (AkMen JURNAL ILMIAH, 2019)
This is the financial performance of Indonesian Civil Servant Cooperative "Widya Enchantment", Operating Capital Expenses to Operating Income, Capital structure, Inventory Turnover, and Liquidity to the financial performance of Indonesian Civil Servant Cooperative. This study uses multiple linear regression analysis of SPSS software, with secondary data from financial statements of Indonesian Civil Servant Cooperative "Widya Pesona" Polytechnic of Tourism of Makassar for three years which is 2015, 2016, and 2017. Results of this study indicate that the Operating Expenses to Operating Income, Inventor Turn over, and Liquidity has a positive and insignificantly affect to the financial performance, however, the Capital structure has been positive and significantly effective to the financial performance of Indonesian Civil Servant Cooperative "Widya Pesona" Polytechnic of Tourism of Makassar